Identification of volatile compounds, antimicrobial properties and antioxidant activity from leaves, cones and stems of Cupressus sempervirens from Algeria - Yousfi, Mohamed; Zouaghi, Nafila; Bellel, Cherifa; Cavaleiro, Carlos; Nadjemi, Boubekeur (African Journal of Microbiology Research, 2015)
L.(Neffati et al., 1999). C. sempervirens is considered to be a medicinal tree, as its dried leaves are used as an emmenagogue and for stomach pain (Castro, 1998), as well as to treat diabetes, and its dried fruit is used to treat inflammation, toothache, and laryngitis as a contraceptive and astringent (Mascolo et al., 1987). In addition, its dried seeds have been used to treat wounds, ulcers, bruises, sores, pimples, pustules, skin eruptions, and erysipelas (Caceres et al., 1987), the branches of this plant are used as antiseptics and antispasmodics (Bellakhder, 1997). The essential oil from the leaves and cones is used externally for headache, colds, cough, and bronchitis. With respect to these medicinal and pharmacological advantages, C. sempervirens is widely used as a cosmetic ingredient in perfumery and soap-making, including its essential oil distilled from shoots (Usher, 1974). C. sempervirens is very widespread